Post Treatment Application of Jaungo after a Combined Therapy of Carbon Dioxide Laser and Trichloroacetic Acid in a Case of Vulvar Syringoma - En Hyung Kim; Wonnam Kim (Korean Pharmacopuncture Institute, 2019)
Syringoma is a benign eccrine sweat gland tumor that predominantly appears in females during puberty with multiple smooth papules measuring 1-2 mm in diameter. Common locations are on lower eyelids and cheeks. Vulvar syringoma is quite a rare, occurring condition with only a few cases reported. Here, we are reporting a case of 31-year-old female with vulvar syringoma associated with pruritus. The lesion was treated with carbon dioxide (CO2) laser ablation and 50% trichloroacetic acid (TCA) chemical peeling. Jaungo was used for wound care after laser abrasion. The combination treatment was effective for removing syringoma lesions. Post laser management with fusidic acid cream and jaungo cream was sufficient to prevent infection and promote wound healing.